Adsorption of Organophosphate Pesticides with Humic Fraction-Immobilized Silica Gel in Hexane - Lai, Yan-Shuo; Chen, Shushi (Journal of chemical and engineering data, 2013)
Fractions collected from humic acid (HA) under acidic conditions and used as adsorbents for various agricultural organophosphate pesticides in hexane are immobilized on silica gel. For most organophosphate analytes examined in this study under the same conditions, the percentage of adsorption achieved nearly 100 % in 1 h and was found to be highly relevant to the structure of the analyte and the type of interaction that occurred between the functional groups attached to it and HA. The interaction leading to adsorption between the functional moieties of the analyte and HA (e.g., P–O or S bond of analyte vs carboxyl group of HA) is believed to be reversible and dipole–dipole oriented and is significantly enhanced in hexane. The enhancement of π–π interaction, even hydrogen bonding in some cases, was also observed in hexane and contributed to the percentage of adsorption to a certain degree. However, the interaction is subject to the steric hindrance effect caused by the bulky group or element surrounding the phosphorus element. Considering the nature of the analyte, the time required to reach the maximum percentage of adsorption is decreased as the amount of adsorbent is increased. Furthermore, the adsorption process is surface oriented because the longer the time that is elapsed, the higher the percent of the analyte that is adsorbed. Factors such as the type of liquid phase or the acidic or basic origin of the additive in the liquid phase of the matrix also affect the adsorption percentage of analyte.